Reticular tapeto-retinal dystrophy. As a possible late stage of Sjögren's reticular dystrophy. Issue 1 (January 1976) - Fishman, G. A.; Woolf, M. B.; Goldberg, M. F.; Busse, B.
Abstract : Findings from two patients with a reticular tapetoretinal dystrophy strongly suggested advanced stages of Sjögren's reticular dystrophy. These observations emphasize that, although initially a benign disease, advanced stages of Sjörgren's dystrophy may eventually manifest diffuse photoreceptor and retinal pigment epithelial disease.